Epilepsies and epileptic syndromes with an unfavorable evolution of febrile crisis antecedents - Albia Josefina Pozo Alonso; Desiderio Rafael Pozo Lauzán (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Febrile crisis occur in 2-5% of children and happened between the ages of 6 months to five years in the absence of central nervous system infection, and previous afebrile seizures. Objective: To describe the main epilepsies and epileptic syndromes with a history of febrile crisis with unfavorable prognosis. Material and Methods: Articles regarding with febrile crisis, epilepsy and epileptic syndromes with a history of febrile crisis with an unfavorable evolution, available in the followings database: Pubmed, Scielo and Imbiomed, were reviewed. Were included in the search for information original research reports and retrospective or prospective and a revision of documents and a book related to the subject mentioned. Articles published in Spanish, English and French were also included. The reviewed period range from 1971 to 2015. Development: There are different epilepsies and epileptic syndromes with a history of febrile crisis which have an unfavorable evolution as Dravet Syndrome, Hemiconvulsion-hemiplegy-epilepsy syndrome, generalized epilepsy with febrile crisis plus, myoclonic-atonic epilepsy, mesial temporal lobe epilepsy, epileptic syndrome, related to febrile infection and epilepsy restricted to girls with or without mental retardation. Conclusions: Although most of the children with febrile crises evolved favorably, shall be considered that some of them may evolve into epilepsies and epileptic syndromes with an unfavorable prognosis. Keywords: Febrile crisis, epilepsy, seizures, syndrome, antecedents.